The Buffer Capacity and Calcium Concentration of Water Influence the Microbial Species Diversity, Grain Growth, and Metabolite Production During Water Kefir Fermentation - Laureys, David; Aerts, Maarten; Vandamme, Peter; De Vuyst, Luc (Frontiers in Microbiology, 2019)
Eight water kefir fermentation series differing in buffer capacity and calcium concentration of the water used for fermentation were studied during eight backslopping steps. High buffer capacities resulted in high pH values and high calcium concentrations resulted in low pH values at the end of each backslopping step. When the water buffer capacity and/or calcium concentration were below certain minima, the water kefir grain growth decreased gradually over multiple backsloppings. High water buffer capacities resulted in high concentrations of residual total carbohydrate concentrations and low metabolite concentrations. Further, high water buffer capacities resulted in high ratios of lactic acid bacteria to yeasts, which was reflected in high molar ratios of the concentrations of lactic acid to ethanol and acetic acid to ethanol. The most prevalent microorganisms of the water kefir grain inoculum and grains of all fermentation series at the end of the eighth backslopping step were Lactobacillus hilgardii, Lactobacillus nagelii, Lactobacillus paracasei, Bifidobacterium aquikefiri, Saccharomyces cerevisiae, and Dekkera bruxellensis. These microbial communities were influenced by the water buffer capacity and had an impact on the substrate consumption and metabolite production during water kefir fermentation.